TASKS OF THE PRODUCT-MIX IN THE MARKETING STRATEGY OF THE VILLAGE CALLED NYÚL - Darabos, Ferenc; Printz-Markó, Erzsébet (PEOPLE: International Journal of Social Sciences, 2018)
In January 2018, the Gyula Kautz Economic Faculty of the István Széchenyi University of Győr was asked to develop the touristic marketing strategy of the settlement called Nyúl. In this study, we analyse the milestones (core elements) of the strategy in due consideration of the product-mix. In our essay, we conducted the initial assessment of the current situation based on other branch and country development strategies using previous primary information. Later, we defined the strategic goals and set the main objectives. The definition of product development tasks is the core element of this study. The analysis of other parts of the marketing-mix is out of scope of this study. This study only covers those elements which determine the marketing-mix. Focusing on the Győr-Vienna-Bratislava triangle, we put a great emphasis on the synergy effect with the neighbouring settlements, especially with Győr and the Abbey of Pannonhalma which is a World Heritage Site. As far as methodological aspects are concerned, we used elements of the integrated settlement development strategy of Nyúl, the country development strategy and the business plans of touristic developments. Our primary research covered the organisation and evaluation of two local workshops in which regional business actors participated.